2017
DOI: 10.1155/2017/9721934
|View full text |Cite
|
Sign up to set email alerts
|

Use of TBzTD as Noncarcinogenic Accelerator for ENR/SiO2 Nanocomposites: Cured Characteristics, Mechanical Properties, Thermal Behaviors, and Oil Resistance

Abstract: This study reported the use of tetrabenzylthiuram disulphide (TBzTD) as a noncarcinogenic accelerator in a traditional sulfur curing system of epoxidized natural rubber (ENR)/nanosilica (nSiO 2 ) composites. ENR used in this work was synthesized via in situ epoxidation of natural rubber (NR) in the presence of performic acid generated from the reaction of formic acid and hydrogen peroxide at 50 ∘ C for 8 h to acquire the epoxide content of about 40 mol%. Accordingly, the resulting ENR was referred to as ENR 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…To determine the mol% epoxidation from the 1 H‐NMR analysis, two characteristic peaks were considered in relation with Eq. 2 ; Mol%0.25emepoxidation=[]A2.7/()A2.7+A5.14×100 where A 2.7 and A 5.14 are the integrate areas under the 1 H‐NMR peaks at about 2.7 ppm, corresponding to the epoxide proton, and at about 5.14 ppm, representing an olefinic proton, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To determine the mol% epoxidation from the 1 H‐NMR analysis, two characteristic peaks were considered in relation with Eq. 2 ; Mol%0.25emepoxidation=[]A2.7/()A2.7+A5.14×100 where A 2.7 and A 5.14 are the integrate areas under the 1 H‐NMR peaks at about 2.7 ppm, corresponding to the epoxide proton, and at about 5.14 ppm, representing an olefinic proton, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It is well established that many desirable properties of rubber products can be achieved through rubber/rubber blend , rubber/polymer blend and rubber composites . It has been reported that latex blending offers compatible or miscible blend without phase separation and flocculation .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations